Media Pembelajaran Pengenalan Hewan Berdasarkan Jenis Makanan Dan Ekosistem Berbasis Augmented Reality - Shandy Tresnawati; Ratna Rizky Wulandari; Cica Tiara (Unit Penelitian dan Pengabdian kepada Masyarakat Politeknik TEDC Bandung Jl. Pesantren Km 2 Cibabat Cimahi Utara – Cimahi 40513 Jawa Barat – Indonesia, 2024)
Early Childhood Education (ECCE) has an important role in shaping the basis of children's knowledge and understanding of the surrounding world, including animal recognition. At Al-Hidayah ECD, animal recognition materials currently use only picture cards, songs, and stories, conducted four times a week. However, there are drawbacks to this method, which is that it only introduces animals based on the letter prefixes of the alphabet and has not introduced the type of food and ecosystem of animals. The results showed that the success rate of animal recognition by students was only 55% with the usual method. In an effort to improve animal recognition methods, this research aims to develop learning media innovations using Augmented Reality (AR) technology with a focus on recognizing animal types based on food and its ecosystem. In this study, researchers chose the Multimedia Development Lyfe Cycle (MDLC) method because this method is suitable for designing and developing multimedia applications. This research was conducted at PAUD Al-Hidayah. The creation of this learning media application was made using the main software Unity 3D. Based on the results of questionnaires filled out by students and teachers, it can be said that animal recognition learning media based on food types and ecosystems that contain video material is equipped with audio, displays 3D animal objects with markers, then contains interestingly made quizzes. The results obtained from the User Acceptance Test (UAT) get results with a percentage of 96.7%. With these positive results, it is hoped that the use of AR for the learning of PAUD Al-Hidayah students can understand more interactive learning.